PENATALAKSANAAN TERAPI BERMAIN LEGO TERHADAP ANAK PRA SEKOLAH DENGAN ANSIETAS PADA ASUHAN KEPERAWATAN DENGUE HEMORRHAGIC FEVER (DHF) - Octarina Piko, Sari; Zalila, Rifka; Santika, Risti (JURNAL SMART ANKes, 2024)
Background : Dengue Hemorrhage Fever (DHF) is the largest disease caused by arboviruses. DHF often attacks preschool children, requiring the child to be in hospital to receive treatment and care until the child recovers. One of the treatments to reduce anxiety is lego play therapy. The lego game is a game in the form of mini-sized colorful plastic blocks that can be arranged into various shapes such as cars, houses, airplanes or robots. Objective: To describe and analyze the provision of distraction techniques through lego play therapy for DHF children with anxiety problems due to hospitalization. Methods: The research design is a descriptive design in the form of a case study. The research subjects used 2 people with the same criteria, namely preschool-aged Dengue Fever pediatric patients who experienced an anxiety nursing problem. This case study was conducted at the Bhayangkara M Hasan Palembang Hospital in 2024. Data collection techniques by means of interviews, observations, and filling out case study instruments for 3 days in the treatment room. Result: Nursing implementation provided in the form of distraction techniques playing lego shows a decrease in anxiety levels marked by verbalization of decreased confusion, verbalization of worry due to conditions faced decreased, restless behavior decreased, tense behavior decreased, concentration improved, sleep patterns improved.